Zone V Extensor Tendon Repair with a Palmaris Longus Tendon Autograft and Human Umbilical Membrane. (4th January 2020) - Esquivel, Esteban; Cox, Cameron; Purcell, Amanda; MacKay, Brendan
Abstract : Extensor tendon repairs, although common, can be difficult injuries to treat. Their treatment is tailored to the zone of the hand that is affected since varying biomechanical forces are applied to the tendon at each zone. Prompt treatment is necessary to prevent potential complications associated with these injuries. This is particularly true of Zone V extensor tendon injuries, as their mechanism is commonly a highly infectious human bite. We present the case of a human fight bite resulting in a Zone V extensor tendon injury. The delayed presentation of this case resulted in an untreated infection that caused an abscess with associated extensor tendon necrosis and rupture. Given the large gap length between the ends of the tendons, tendon repair was performed using a palmaris longus autograft. Even when these are done in a controlled setting, adhesions are common. The compromised wound bed caused irritation, erosion, and subsequent rupture of the extensor tendon of the hand. In an effort to avoid common complications such as adhesion, the repair was then wrapped with human umbilical membrane (AVIVE® Soft Tissue Membrane, AxoGen Inc., Alachua, FL) to separate adjacent tissue and reduce inflammation. Even without access to formal physical therapy, our patient had excellent functional outcomes at his final follow-up visit. The patient was able to make a loose composite fist, had no extensor lag at the MCP joints, and had extensor lag of 15 degrees at the PIP joints of digits 4-5.